2021
DOI: 10.1519/jsc.0000000000003218
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Mood States Associated With Outcomes Achieved by Female and Male Athletes in High-Level Judo and Brazilian Jiu-Jitsu Championships: Psychological Factors Associated With the Probability of Success

Abstract: Comparisons of mood states associated with outcomes achieved by female and male athletes in high-level judo and Brazilian jiujitsu championships: psychological factors associated with the probability of success. J Strength Cond Res 35(9): 2518-2524, 2019-Moods can be used to predict the performance of athletes in various sports; accordingly, we selected the Brunel Mood Scale (BRUMS) to evaluate mood states of high-level judo and Brazilian jiu-jitsu (BJJ) athletes. The aims of this study were (a) to compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Simultaneously, it is becoming evident that judo fighter suffering from depression, and post-traumatic stress could display structural anomalies and unusual functional coupling within the hippocampal-prefrontal circuit (Godsil et al, 2013). This overlap might similarly be intertwined with the pathway's evident susceptibility to stress and with its relationship to the amygdala, associated with anxiety and mood disorders (Kirkbride et al, 2012) in judo/Brazilian jiu-jitsu (Brandt et al, 2019) and MMA athletes (Brandt et al, 2018). In consequence, the H-PFC pathway could be a potentially crucial element of the anxiety in judo athletes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simultaneously, it is becoming evident that judo fighter suffering from depression, and post-traumatic stress could display structural anomalies and unusual functional coupling within the hippocampal-prefrontal circuit (Godsil et al, 2013). This overlap might similarly be intertwined with the pathway's evident susceptibility to stress and with its relationship to the amygdala, associated with anxiety and mood disorders (Kirkbride et al, 2012) in judo/Brazilian jiu-jitsu (Brandt et al, 2019) and MMA athletes (Brandt et al, 2018). In consequence, the H-PFC pathway could be a potentially crucial element of the anxiety in judo athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Preceding authors have developed anxiety traits questionnaires that were especially tailored to sports and was denominated as the sport competition anxiety test (SCAT) used in karate (Terry and Slade, 1995) and judo with higher values for female than male athletes (Wong et al, 2006;Interdonato et al, 2013). Recently, comparisons of mood states, using the Brunel Mood Scale (BRUMS), associated with outcomes achieved by female and male athletes in high-level judo and Brazilian jiu-jitsu (BJJ) championships demonstrated that female judo athletes had higher depression and vigor index than BJJ athletes (Brandt et al, 2019), while the logistic regression revealed that higher levels of anger and tension increased athletes' chances of performing well in a match by 23% and 13%, respectively (Brandt et al, 2019). Overall, authors observed a significant relationship between mood state and sports performance (Brandt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are contradictory results on the influence of anger on athlete performance. Páez-Ardila et al [ 34 ] showed that judokas with increased anger were those who were defeated, while higher levels of anger improved the chances of better performance in individual and team sports [ 42 , 43 ]. Furthermore, the vigor deficit reduces the probability of winning [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…To summarize, compared to male athletes, female athletes appeared to be at an increased risk to report negative psychological emotions (i.e., feelings of inadequacy, negative self-judgment and emotional disruption) and poorer performance [ 62 , 63 , 64 , 65 ]. Mindfulness-based interventions in general, and MAC, specifically, proved to be useful to counterbalance dysfunctional emotional states [ 1 , 66 , 67 , 68 ] and to improve psychological wellbeing [ 50 , 69 ].…”
Section: Introductionmentioning
confidence: 99%